2016
DOI: 10.1016/j.eurpsy.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioral difficulties in children growing up homeless in Paris. Results of the ENFAMS survey

Abstract: Purpose: Children growing up in homeless families are disproportionately more likely to experience health and psychological problems. Our objective was to describe social, environmental, individual and family characteristics associated with emotional and behavioral difficulties among homeless children living in the Paris region.Methods: Face-to-face interviews with a representative sample of homeless families were conducted by bilingual psychologists and interviewers between January and May 2013 (n=343 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Furthermore, 35.9% of our study sample were survivors of rape or sexual assault. It is important to note the growing amount of literature documenting the association between mothers' mental health and children's emotional difficulties [41], highlighting the importance of maternal PTSD on their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 35.9% of our study sample were survivors of rape or sexual assault. It is important to note the growing amount of literature documenting the association between mothers' mental health and children's emotional difficulties [41], highlighting the importance of maternal PTSD on their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Social exclusion and the other previously stated factors are also connected with poor educational outcomes (Roze et al , 2016). Frequent episodes of homelessness negatively impact the educational trajectories of children (Gültekin et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This survey reported that nearly all these women (94%) were born outside of France (63% in Africa); 94% lived below the poverty level; and about half in single-parent families. The survey highlighted major health problems in both mothers and their children, such as high rates of food insecurity, malnutrition and mental health disorders (Arnaud et al, 2018;Martin-Fernandez et al, 2018;Roze et al, 2018Roze et al, , 2016Vandentorren et al, 2016).…”
Section: Introductionmentioning
confidence: 99%